Perancangan Aplikasi Multimedia Flash Peta Provinsi Indonesia di SDN Gurubug 1 Tangerang - Rukmana, Irman; Susila, Mochamad Nandi (LPPM STMIK ANTAR BANGSA, 2017)
Abstract—Supporting learning media for elementary school students have many variations of the technique of delivery, whether there is in the form of video or audio media. One of the medium of delivery for students' learning, namely multimedia-based application design that becomes in this research. The ability to recognize the geographic province of Indonesia for primary level need to be developed so that students are able to easily find out properly the province of Indonesia, this aims in this study, namely, designing a multimedia application map province of Indonesia. By using the techniques of observation and data collection in library studies, objects in this research is SDN Gurubug 1 Tangerang, where students made the main reference in support of the design of this application. The design of multimedia applications research using model waterfall in application development. As for the testing phase of the application, testing techniques researchers are using black box testing. The results of this study, the application of the multimedia map of the Indonesian province for students Gurubug SDN 1 Tangerang help in the knowledge of the existing provinces in Indonesia. Intisari—Media pendukung pembelajaran bagi siswa sekolah dasar memiliki banyak variasi teknik penyampaian, baik ada yang berbentuk media audio maupun video. Salah satu media penyampaian bagi pembelajaran siswa yaitu berbasis multimedia yang menjadi rancangan aplikasi dalam penelitian ini. Kemampuan mengenali geografis provinsi Indonesia bagi tingkat sekolah dasar perlu dikembangkan agar siswa mampu dengan mudah mengetahui dengan baik provinsi Indonesia, hal ini yang menjadi tujuan dalam penelitian ini, yaitu merancang suatu aplikasi multimedia peta provinsi Indonesia. Dengan menggunakan teknik pengumpulan data observasi dan studi kepustakaan, objek dalam penelitian ini adalah SDN Gurubug 1 Tangerang, dimana siswa-siswi dijadikan acuan utama dalam mendukung perancangan aplikasi ini. Perancangan aplikasi multimedia penelitian ini menggunakan model waterfall dalam pengembangan aplikasi. Sedangkan untuk tahap pengujian aplikasi, peneliti menggunakan teknik pengujian black box testing. Hasil dari penelitian ini, yaitu, aplikasi multimedia peta provinsi indonesia untuk siswa SDN Gurubug 1 Tangerang membantu dalam pengetahuan mengenai provinsi-provinsi yang ada di Indonesia.Kata Kunci— Aplikasi Multimedia Flash, Provinsi Indonesia, Model Waterfall